Sex-Specific Limitations in Physical Health in Primary Adrenal Insufficiency - Didriksen, Nora Møller; Sævik, Åse Bjorvatn; Sortland, Linn Solveig; Øksnes, Marianne; Husebye, Eystein Sverre (Frontiers in Endocrinology, 2021)
Background: Patients with primary adrenal insufficiency (PAI) suffer reduced quality of life (QoL), but comparisons with large-scale normative data are scarce. The clinical characteristics associated with reduced QoL are largely unknown. Methods: Cross-sectional data on clinical characteristics and QoL scores from 494 patients were included. QoL was measured using RAND-36 (generic) and AddiQoL (-30 and -8, disease-specific). RAND-36 is reported as subdomain scores as well as physical (PCS) and metal (MCS) summary scores and compared with normative data. Results: Perception of physical role was consistently decreased across age groups in patients with PAI compared with normative data (75 [0-100] vs. 100 [50-100], p<0.001). Men with PAI reported significantly lower scores for social functioning (88 [75-100] vs. 100 [75-100], p<0.001), as well as for vitality and physical role. In women, the greatest impairment was seen in physical role (50 [0-100] vs. 100 [50-100], p<0.001), followed by social functioning, vitality, physical function, general health, mental health, and emotional role. Overall, better QoL was associated with male sex (AddiQoL-30: 89 ± 13 vs. 82 ± 13, p<0.002), younger age (e.g. 20-29 vs. 80-89 years: PCS 59 [50-62] vs. 46 [37-53], p<0.001), autoimmune etiology (PCS: 53 [45-59] vs. 45 [38-54], p<0.001), and absence of autoimmune comorbidity (PCS: 54 [45-59] vs. 50 [43-58], p<0.001). There were no significant differences in QoL scores between different doses or dosing regimens of glucocorticoid or mineralocorticoid replacement. Conclusion: QoL is reduced in patients with PAI, especially perception of physical role in women and social functioning in men. Among patients with PAI, female sex, higher age, non-autoimmune etiology, and autoimmune comorbidity was associated with lower QoL-scores.